2021
DOI: 10.1002/mnfr.202100337
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Improved Activity of Natural Killer Cells Induced by the Consumption of F‐MRP for 8 weeks

Abstract: Scope: The authors used metabolomics to investigate the nutritional modulatory effect of fermented Maillard-reactive whey protein (F-MRP) on the activity of natural killer (NK) cells. Methods and Results: Fifty subjects who had participated in our previous intervention study were included in the present study in the test (n = 20) and placebo groups (n = 30). Additional analyses using ultra performance liquid chromatography-mass spectrometry (UPLC-MS) and gas chromatography (GC)-MS were conducted to identify re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Our review also identified 76 studies of leukocyte levels and measures of leukocyte activity, proliferation, cytotoxicity and phagocytosis (Supplemental Table 3 , Additional file 3 ) and 47 studies of cytokine production (Supplemental Table 4 , Additional file 3 ). Five instances were identified where two publications reported results from the same study [ 28 , 55 , 56 , 67 73 ]; however, both publications were included because they provided unique data. Future publications will discuss other immune-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Our review also identified 76 studies of leukocyte levels and measures of leukocyte activity, proliferation, cytotoxicity and phagocytosis (Supplemental Table 3 , Additional file 3 ) and 47 studies of cytokine production (Supplemental Table 4 , Additional file 3 ). Five instances were identified where two publications reported results from the same study [ 28 , 55 , 56 , 67 73 ]; however, both publications were included because they provided unique data. Future publications will discuss other immune-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In GSVA, the downregulation of PTGS2 expression was significantly associated with various pathways [ 51 ], including folate biosynthesis, dorsoventral axis formation, renal cell carcinoma, regulation of autophagy, glycosphingolipid biosynthesis (lacto and neolacto series), pantothenate and CoA biosynthesis, and O-glycan biosynthesis. The downregulation of PLA2G7 expression was significantly associated with aminoacyl tRNA biosynthesis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%